Registration of Transfer of Property Rights to Land by Buying and Selling and the Problems - Priyo Harsono (Universitas Islam Sultan Agung, 2020)
This study aims to determine the practice of registering the transfer of title to land in the Tegal Regency Land Office and the efforts made if the registration of the transfer of land rights is late and the efforts made by land buyers to register the transfer of rights if the sale is carried out under the hands and how the legal protection is carried out. if not registered at the Land Office.The approach method used in this research is sociological juridical with analytical descriptive research specifications, as for complementing the data, non-random sampling is carried out by taking samples and conducting direct interviews (interviews) that are free of charge to parties related to land registration.The results of the study of the problem in this thesis are that there are still delays in registering the transfer of land ownership by way of selling and buying under hand. Delays in registering the transfer of rights at the Tegal Regency Land Office are still often carried out by the Camat as PPAT officials due to his busyness in the Government, for this it is the obligation of land buyers to complete their deeds by making a statement of delay, a statement of physical ownership and a statement of not being in dispute. As for land buyers are often disadvantaged by carrying out the sale and purchase under hand, because when the deed is to be made, the seller has passed away or where his residence is not known, the solution in order to register the transfer of his rights is to use a court decision which has permanent legal force.Keywords: Transfer of Rights Registration; Right of ownership; Sale and Purchase of Land;